1998
DOI: 10.1006/anbo.1998.0704
|View full text |Cite
|
Sign up to set email alerts
|

Seed Structure and Localization of Reserves inChenopodium quinoa

Abstract: The three areas of food reserves in quinoa seeds are : a large central perisperm, a peripheral embryo and a one to twocell layered endosperm surrounding the hypocotyl-radicle axis of the embryo. Cytochemical and ultrastructural analysis revealed that starch grains occupy the cells of the perisperm, while lipid bodies, protein bodies with globoid crystals of phytin, and proplastids with deposits of phytoferritin are the storage components of the cells of the endosperm and embryo tissues. EDX analysis of the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
150
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(166 citation statements)
references
References 32 publications
9
150
0
7
Order By: Relevance
“…Similar observations have been previously reported. 5,6) In this study, we found that Ca occurred mostly in the pericarp and seed coat as well as in the boundary between perisperm and embryo (Fig. 1).…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Similar observations have been previously reported. 5,6) In this study, we found that Ca occurred mostly in the pericarp and seed coat as well as in the boundary between perisperm and embryo (Fig. 1).…”
supporting
confidence: 54%
“…In quinoa seeds, it has been observed that phytin globoids are included in protein bodies of embryonic cells and that P, Mg, and K are localized in the globoids with energy dispersive X-ray (EDX) analysis. 5,6) These analyses, however, were done by point analysis which involves analyzing areas of the size of the electron beam. In the aspect of mineral nutrition, we need the information of the overall distribution of mineral nutrients in whole quinoa seeds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the rice prolamins are isolated in Type I protein bodies (Saito et al, 2012) and the glutelins are isolated in Type II protein bodies (Yamagata et al, 1982) and in oats the globulin and prolamin storage proteins are co-located in the same protein bodies (reviewed by . The albumin and globulin storage proteins of the pseudocereals, amaranth (Coimbra and Salema, 1994), buckwheat (Elpidina et al, 1990) and quinoa (Prego et al, 1998) are also isolated in protein bodies. The localisation of storage proteins in discrete protein bodies in these "gluten-free" grains is unlike the situation in wheat where the glutenin and gliadin proteins form a continuous matrix around the starch granules within the cells of the mature starchy endosperm (reviewed by .…”
Section: Isolation In Protein Bodiesmentioning
confidence: 99%
“…For quinoa seeds (~15 w/dw% protein), it is extremely difficult to separate protein bodies from starch granules as these are similar in size (Prego et al 1998). However, quinoa protein bodies are concentrated in the embryo of the seed (~23.5 w/dw% protein), while starch granules are concentrated in the perisperm (Ando et al 2002).…”
Section: Introductionmentioning
confidence: 99%